UJI TOLERANSI GALUR KACANG TANAH HASIL IRADIASI SINAR GAMMA TERHADAP LARUTAN POLIETILENA GLIKOL - A. Farid Hemon; Syarifinnur Syarifinnur; Lestari Ujianto; Sumarjan Sumarjan (JURNAL AGROTROPIKA, 2012)
The objective of this research was to evalu-ate the tolerance of peanut lines generated from Gamma ray iradiation against polyethylene glycol (PEG) solution stress. The peanut lines seeds of mutan M3 generation were used in this experiment. Peanut plants of cv. “Local Bima” were also tested as control plant. The mutan and control peanut plants were planted on rice hush charcoal medium. The peanut plants that 15 to 50 days old were watered with PEG 15% solution (0.41 Mpa osmotic potential = drought stress). Identification of tolerant peanut lines on PEG stress were calculated with using drought sensitivity index value (S) on observed parameter and proline content. Results of the experiment showed that peanut line G300 was classified as moderate tolerant to PEG solution stress with the highest proline content. Keywords : peanut lines, gamma ray, mutan, polyethylene glycol